Haikai poet Yosa Buson and the Bash?o revival - Crowley, Cheryl A. (Brill's Japanese studies library, 2007)
Uses the haikai verse and paintings of the brilliant, innovative artist Yosa Buson as a focal point from which to explore how early modern Japanese writers competed for artistic authority and social prestige. This book concludes with a discussion of Buson's reception in the modern period, and includes translations of his principal works.